Bacteria‐Based Cancer Immunotherapy - Xuehui Huang; Jingmei Pan; Funeng Xu; Binfen Shao; Yi Wang; Xing Guo; Shaobing Zhou (Advanced Science, 2021)
Abstract In the past decade, bacteria‐based cancer immunotherapy has attracted much attention in the academic circle due to its unique mechanism and abundant applications in triggering the host anti‐tumor immunity. One advantage of bacteria lies in their capability in targeting tumors and preferentially colonizing the core area of the tumor. Because bacteria are abundant in pathogen‐associated molecular patterns that can effectively activate the immune cells even in the tumor immunosuppressive microenvironment, they are capable of enhancing the specific immune recognition and elimination of tumor cells. More attractively, during the rapid development of synthetic biology, using gene technology to enable bacteria to be an efficient producer of immunotherapeutic agents has led to many creative immunotherapy paradigms. The combination of bacteria and nanomaterials also displays infinite imagination in the multifunctional endowment for cancer immunotherapy. The current progress report summarizes the recent advances in bacteria‐based cancer immunotherapy with specific foci on the applications of naive bacteria‐, engineered bacteria‐, and bacterial components‐based cancer immunotherapy, and at the same time discusses future directions in this field of research based on the present developments.